PERTIMBANGAN DESAIN DAN ESTIMASI GAYA APUNG DAN GAYA TENGGELAM PADA RUMPON DI PERAIRAN PANDEGLANG, PROVINSI BANTEN - Ronny I. Wahyu; Budhi H. Iskandar; Erwan N. Wahyudin (Institut Pertanian Bogor, 2009)
Research on design considerations and estimation of forces of fish aggregating device was carried out in Pandeglang water’s Banten Province. The main construction of fish aggregating de-vice consists of pontoon, wire, main line, attractor (coconut leaf), and sinker (main, bet-ween,attractant). Total buoyancy force is estimated 2.743.896,59 gs, and total sinking force is 1.006.888,74 gs thefore the extra buoyancy force is 63.30%. The buoyancy and sinking forces are smaller than breaking strength main line (6.500.000 gs), the main line still resistance in maximum condition of buoyancy and sinking force.Key word: buoyancy force, fish aggregating device, sinking force